Spinodal decomposition versus classical γ′ nucleation in a nickel-base superalloy powder: An in-situ neutron diffraction and atomic-scale analysis. (November 2020) - Collins, David M.; D'Souza, Neil; Panwisawas, Chinnapat; Papadaki, Chrysanthi; West, Geoff D.; Kostka, Aleksander; Kontis, Paraskevas
Graphical abstract: Abstract: Contemporary powder-based polycrystalline nickel-base superalloys inherit microstructures and properties that are heavily determined by their thermo-mechanical treatments during processing. Here, the influence of a thermal exposure to an alloy powder is studied to elucidate the controlling formation mechanisms of the strengthening precipitates using a combination of atom probe tomography and in-situ neutron diffraction. The initial powder comprised a single-phase supersaturated γ only; from this, the evolution of γ ′ volume fraction and lattice misfit was assessed. The initial powder notably possessed elemental segregation of Cr and Co and elemental repulsion between Ni, Al and Ti with Cr; here proposed to be a precursor for subsequent γ to γ ′ phase transformations. Subsolvus heat treatments yielded a unimodal γ ′ distribution, formed during heating, with evidence supporting its formation to be via spinodal decomposition. A supersolvus heat treatment led to the formation of this same γ ′ population during heating, but dissolves as the temperature increases further. The γ ′ then reprecipitates as a multimodal population during cooling, here forming by classical nucleation and growth. Atom probe characterisation provided intriguing precipitate characteristics, including clear differences in chemistry and microstructure, depending on whether the γ ′ formed during heating or cooling.